Preventing Cardiovascular Complications in Type 1 Diabetes: The Need for a Lifetime Approach - Chiesa, Scott T.; Marcovecchio, M. Loredana (Frontiers in Pediatrics, 2021)
Cardiovascular disease (CVD) remains the main cause of morbidity and mortality in individuals with type 1 diabetes (T1D). Adolescence appears to be a critical time for the development of early subclinical manifestations of CVD, with these changes likely driven by a transient deterioration in glycemic control during the progression through puberty, combined with the emergence of numerous other traditional cardiometabolic risk factors (e.g. hypertension, dyslipidemia, smoking, alcohol use, obesity, etc) which emerge at this age. Although hemoglobin A1C has long been the primary focus of screening and treatment strategies, glycemic control remains poor in youth with T1D. Furthermore, screening for cardiovascular risk factors – which are often elevated in youth with T1D – is suboptimal, and use of pharmacological interventions for hypertension and dyslipidemia remains low. As such, there is a clear need not only for better screening strategies for CVD risk factors in youth, but also early interventions to reduce these, if future CVD events have to be prevented. Accumulating evidence has recently suggested that early increases in urinary albumin excretion, even within the normal range, may identify adolescents with T1D who are at an increased risk of complications, and results from pharmacological intervention with statins and ACE inhibitors in these individuals have been encouraging. These data join a growing evidence base highlighting the need for a whole-life approach to prevention starting from childhood if efforts to improve CVD outcomes and related mortality in T1D are to be maintained.